2021
DOI: 10.1111/epi.17025
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic tractography‐based localization of spike sources and animation of spike propagations

Abstract: Objective: This study was undertaken to build and validate a novel dynamic tractography-based model for localizing interictal spike sources and visualizing monosynaptic spike propagations through the white matter. Methods:This cross-sectional study investigated 1900 spike events recorded in 19 patients with drug-resistant temporal lobe epilepsy (TLE) who underwent extraoperative intracranial electroencephalography (iEEG) and resective surgery.Twelve patients had mesial TLE (mTLE) without a magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“… 30 IEDs have often been observed in the lateral temporal cortex beyond the mesial temporal structures and sometimes beyond the surgical resection areas, and these propagations were correlated with unfavourable seizure outcomes after surgery. 31 Furthermore, the cumulative evidence indicated that the selective treatment to the HIP or to the mesial temporal structures were inferior to the anterior temporal lobectomy in terms of the chance of seizure freedom. 32 , 33 The finding of the elevated uptake of [ 11 C]K-2 in the lateral temporal cortex might be useful for the prediction of treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 30 IEDs have often been observed in the lateral temporal cortex beyond the mesial temporal structures and sometimes beyond the surgical resection areas, and these propagations were correlated with unfavourable seizure outcomes after surgery. 31 Furthermore, the cumulative evidence indicated that the selective treatment to the HIP or to the mesial temporal structures were inferior to the anterior temporal lobectomy in terms of the chance of seizure freedom. 32 , 33 The finding of the elevated uptake of [ 11 C]K-2 in the lateral temporal cortex might be useful for the prediction of treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We acquired iEEG and MRI data using methods, as reported previously ( Nakai et al, 2017 ; Mitsuhashi et al, 2021 ). We placed platinum disk electrodes (10 mm center-to-center distance) on the pial surface of the brain ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The FreeSurfer script ( http://surfer.nmr.mgh.harvard.edu ) spatially normalized given electrode sites to standard Montreal Neurological Institute (MNI) space ( Fig. 2 ; Ghosh et al, 2010 ; Mitsuhashi et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations